Hubungan Antara Keterampilan untuk Sukses dan Prestasi Akademik Siswa Madrasah Aliyah Kabupaten Situbondo - Hanik Mufaridah (Program Pascasarjana Universitas Ibrahimy, 2017)
The purpose of this study is to find out empirical evidence of the relationship between skills for success and academic achievement of Islamic Senior High School students in Situbondo regency. Data were collected with self-discipline scale, self-efficacy scale, need for achievement scale, self-control ability scale, time management skill scale, problem solving skill scale and scores of mathematics, physics, chemistry and biology which analyzed by Spearman correlation. The sample was obtained by using multistage random sampling technique. The results of studies from various literatures conclude that self-discipline, self efficacy, need for achievement, self-control ability, time management skills, and problem solving skills have a significant positive relationship with students’ achievement. And from the findings that will be obtained, there is one factor from the six factors that contribute greatly to the students’ academic achievement, so that factor will need to get attention especially from the teachers.